Characterization of Open Cell Aluminium Foam Structure for Different Pore Sizes Fabricated by Infiltration Process. (2018) - Suresh, C.; Vidyashankar, S.; Maruthi, B.H.
Abstract: Open cell aluminium foam specimens were produced through infiltration process by open metal die casting using soil granules of different diameter as space holder particles (SHP). The SHP balls were removed from the Al foam by water jet along with vibration. Aluminium foams which were developed by using different geometry moulds of which the flat specimens were for compression strength testing and cubical specimens were for fluid flow test.For analyzing the compressive behaviour of Aluminium foams flat specimens were developed using ASTM standard specimen size and the compression test was done on universal testing machine (UTM). For specimen of different SHP diameter the compressive behaviour were noted for the developed Al foam. The fluid flow and pressure drop properties were found out using wind tunnel experimental setup.